Kaempferol Derivatives from Hedychium gardnerianum : Unveiling the Potential of an Invasive Plant - Tavares, Wilson R. (2022)
The therapeutic properties of plants and of their secondary metabolites are a current research topic of great interest. Considering that Hedychium species are used in folk medicine around the globe, Hedychium gardnerianum Sheppard ex Ker Gawl., an extremely aggressive invasive plant in Hawaii and in Azores, was selected and phytochemically studied in order to search for natural compounds with interesting biological activities. […].